2021
DOI: 10.1103/physrevb.104.165308
|View full text |Cite
|
Sign up to set email alerts
|

Temporally modulated metamaterial based on a multilayer graphene structure

Abstract: The recently developed concept of time-varying metamaterials paves the way for advanced methods of electromagnetic property modulation, such as magnet-free isolators, frequency converters, and other nonreciprocal photonic components. Here, we analyze the metamaterial based on the periodically arranged temporally modulated graphene layers via a steplike graphene Fermi level. The material properties are described by the effective medium theory. The electromagnetic wave temporal scattering phenomenon caused by ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The adoption of topological materials, such as graphene and TI, in periodic multilayered structure has been recently investigated. The applicabilities of graphene multilayers for frequency conversion and electromagnetic wave absorption have been studied [22,23], and it is also found that the TI effects can be accumulated in multilayered structures [24]. High Chern number phase behavior [25] and tunable spontaneous emission interference [26,27] can be achieved in the TI multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of topological materials, such as graphene and TI, in periodic multilayered structure has been recently investigated. The applicabilities of graphene multilayers for frequency conversion and electromagnetic wave absorption have been studied [22,23], and it is also found that the TI effects can be accumulated in multilayered structures [24]. High Chern number phase behavior [25] and tunable spontaneous emission interference [26,27] can be achieved in the TI multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Optical characteristics of PNJs and TJs are governed by the index of refraction, geometry, and size of the generating micro-object 52 55 as well as the refractive index of the material around the micro-object 56 and properties of the incident light 2 , 57 . Refractive index can be modulated through incorporation of core–shell geometries 58 , 59 , liquid crystals 60 , 61 , temperature-sensitive vanadium oxide (VO 2 ) coating 62 , and graphene coating 63 , 64 in dielectric micro-objects in order to produce tunable PNJs and TJs. Although these approaches allow dynamic control of the refractive index, they are associated with their own features and principles of operation, for example slow response time (typically on the order of milliseconds) in liquid crystals 65 , control by precise change in the temperature in VO 2 (a phase change material), and the need to fabricate graphene with single-atom-layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous approaches have involved mostly metamaterials exhibiting antireflective properties and absorption resonances (thus narrow-band operation) [12][13][14][15]. Some of the proposed metamaterials structures have also featured multilayer graphene sheets [16][17][18]. High-porosity three-dimensional (3D) graphene materials have been demonstrated to exhibit excellent wide-angle absorbing properties in the range below 1 THz [19].…”
Section: Introductionmentioning
confidence: 99%